The efficacy of tranexamic acid in melasma: A review - Sari, Ninda; Putri, Rachmah Diana; Syahrir, Syahriani; Agustina, Agustina; Bulqiah, Mikyal (Journal of General - Procedural Dermatology and Venereology Indonesia, 2025)
Background: Melasma is a common acquired pigmentary condition presenting as dark macules or patches on sun-exposed areas of the face. Conventional treatments rely on topical bleaching agents and sun protection, while additional adjuvant options such as chemical peels, dermabrasion, and laser procedures are often applied. However, recurrence is frequent, and overall therapeutic success remains modest, significantly affecting patient quality of life. Recently, tranexamic acid (TXA) has gained attention as a novel therapeutic approach. This review provides an overview of the available evidence on the efficacy of TXA, used as monotherapy or in combination regimens, for the management of melasma. Discussion: TXA has been investigated for administration via several routes, including oral, intradermal, and topical. The pathophysiology of melasma involves not only abnormal melanogenesis but also enhanced dermal vascularity and angiogenic activity. TXA acts by interfering with the plasminogen–plasmin system, thereby altering keratinocyte–melanocyte signaling and reducing melanogenesis. In addition, it demonstrates anti-angiogenic effects, leading to reduced vessel density and erythema. Clinical data suggest oral TXA generally yields superior outcomes compared to intradermal or topical approaches, although study results remain heterogeneous, particularly in trials combining multiple therapies. Conclusion: TXA appears to be a promising therapeutic option for melasma, with potential use as a stand-alone intervention or in combination with other modalities. Combination regimens often produce better clinical improvement than monotherapy. Nonetheless, standardized guidelines for the optimal use of TXA in melasma treatment remain lacking.